SEJARAH MASJID SULTAN HASSAN: ANALISIS DAN KONSEP DESIGN SEBAGAI REPRESENTASI SOSIAL BUDAYA DI KAIRO - Muhamad Khafifudin (ADISAM PUBLISHER, 2026)
The Sultan Hassan Mosque in Cairo is one of the most significant examples of Islamic architecture, not only due to its high aesthetic value but also as a representation of the social and cultural dynamics of the Mamluk period. This study aims to analyze the mosque’s architecture and its role as a center for social, educational, and economic activities within the surrounding community. The findings of this study indicate that the Sultan Hassan Mosque embodies the close relationship between architecture and Islamic social systems. The mosque complex is not only a symbol of Mamluk architectural grandeur but also serves as a hub for community life that supports social, educational, and economic sustainability. Thus, the mosque stands as evidence of how religious buildings can play a vital role in the development of Islamic civilization.